Managing pharmaceutical regulation in Germany: Overview and economic assessment - Jonas Schreyögg; Klaus-Dirk Henke; Reinhard Busse (Technische Universität Berlin, Fakultät Wirtschaft und Management, 2004)
Rising costs in pharmaceutical expenditure have become a major concern for policy makers in Germany over the last years. Therefore the pharmaceutical market in Germany has been increasingly targeted by different kinds of regulations, focussing both on the supply and the demand side, using price, volume and spending controls. Specific regulations include price reductions, reference pricing, pharmacy rebate for sickness funds, increasing co-payments, an "aut-idem" substitution, parallel imports, negative list, guidelines, and finally spending caps for pharmaceutical expenditure per physicians' association. Although it is difficult to attribute certain effects to single measures, some measures like reference pricing and physician spending caps are more effective and long-lasting than others. Although highly disputed among physicians, the spending caps applied between 1993 and 2001 have limited pharmaceutical expenditure for an entire decade. However, while some measures do effectively control expenditures, their effect on allocative efficiency may be negative. – – Steigende Ausgaben für Arzneimittel stellen zunehmend ein Problem für Entscheidungsträger in Politik und Selbstverwaltung dar. Daher war der Arzneimittelmarkt in den letzten Jahren Ziel verschiedener Regulierungsformen, die sowohl auf der Angebotsseite als auch auf der Nachfrageseite ansetzen und sowohl Instrumente zur Preis, Mengen als auch Ausgabenregulierung nutzen. Sie umfassen dabei insbesondere Preisrabatte, Festbeträge, Zuzahlungen, "Aut-idem" substitution, Parallelimporte, Negativlisten, Leitlinien and Arzneimittelbudgets. Obwohl es schwierig ist, bestimmte Wirkungen monokausal auf einzelne Maßnahmen zu zurückzuführen, kann festgestellt werden, dass Arzneimittelbudgets und Festpreise nachhaltiger und effektiver als andere Regulierungsformen sind. Obwohl Arzneimittelbudgets bei niedergelassenen Ärzten sehr umstritten sind, waren sie hauptverantwortlich für die Begrenzung der Arzneimittelausgaben zwischen 1993 und 2001. Daneben existieren einige Regulierungsformen die zwar die Arzneimittel-ausgaben wirksam senken, deren allokative Effizienz jedoch insgesamt eher negativ ist.
Keywords: 330; Arzneimittelmarkt; Regulierung; Gesundheitskosten; Wirkungsanalyse; Deutschland